Management of Recalcitrant Cutaneous Warts: A Narrative Review of HPV Vaccination and Intralesional Therapies - Sobczak, Agnieszka; Szczot, Alicja; Jaworowicz, Anna; Piasecka, Joanna; Gołembiewski, Bartosz; Mulski, Grzegorz; Manicka, Martyna; Baranowicz, Michał; Mazurkiewicz, Weronika; Borecka, Zuzanna (Quality in Sport, 2026)
Background: Cutaneous warts caused by human papillomavirus (HPV) are among the most prevalent dermatological conditions, with up to one third of non-genital lesions becoming recalcitrant to conventional destructive therapies. The limited efficacy of treatment and high recurrence rates associated with first-line modalities have driven growing interest in immunotherapeutic approaches. Methods: This narrative review was conducted following a structured literature search of PubMed database, covering publications from January 2016 to March 2026, with the aim of synthesizing current evidence on intralesional immunotherapy and HPV vaccination in the management of recalcitrant extragenital cutaneous warts. Results: Among intralesional agents, the MMR vaccine demonstrates the most consistent efficacy, with pooled complete response rates of 63.2% and distant wart clearance in 62.0% of patients. Intralesional HPV vaccination achieved the highest complete response rate in a placebo-controlled trial (75%), with a favorable safety. The evidence for intralesional vitamin D3 is heterogeneous; the sole double-blind, placebo-controlled trial showed no significant benefit over placebo. Therapeutic intramuscular HPV vaccination achieved complete resolution in 61.2% of patients across available studies, while routine prophylactic vaccination status did not influence wart resolution in standard treatment settings. Conclusions: Intralesional MMR and HPV vaccines represent the most promising therapeutic modalities for recalcitrant cutaneous warts. Standardization of treatment protocols and large multicentre randomized controlled trials are required to establish definitive evidence-based recommendations.